2008
DOI: 10.1007/s00266-008-9182-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Poly-L-Lactic Acid Implant for Treatment of the Nasolabial Fold: 3-Year Follow-Up Evaluation

Abstract: The search for an ideal filler for soft tissue augmentation still continues. Because aging changes are continuous, temporary fillers should be preferred against permanent ones. Since 1999, the poly-L-lactic acid filler (PLA) has been marketed in Europe as Newfill. As a synthetic biocompatible polymer, PLA originally was used in suture materials and screws. In 2004, the U.S. Food and Drug Administration approved PLA under the name of Sculptra for the treatment of human immunodeficiency virus-related facial lipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 10 publications
0
31
0
Order By: Relevance
“…Therefore, injections into the dermis, particularly in thin dermis areas, such as upper lip, lower eyelids, glabella, and superficial wrinkles from the cheeks, are localizations with a high risk for any adverse event [35]. A rare complication due to the injection of PLLA is a foreign-bodyinduced granulomatous reaction, which can persist for several years [35,64]. This delayed hypersensitivity reaction to the product also can be associated with persisting itching, edema, and erythema [65].…”
Section: Adverse Events Related To Temporary Fillersmentioning
confidence: 99%
“…Therefore, injections into the dermis, particularly in thin dermis areas, such as upper lip, lower eyelids, glabella, and superficial wrinkles from the cheeks, are localizations with a high risk for any adverse event [35]. A rare complication due to the injection of PLLA is a foreign-bodyinduced granulomatous reaction, which can persist for several years [35,64]. This delayed hypersensitivity reaction to the product also can be associated with persisting itching, edema, and erythema [65].…”
Section: Adverse Events Related To Temporary Fillersmentioning
confidence: 99%
“…Finally, a recently published small-scale European trial by Salles et al 30 assessed the use of injectable PLLA for the aesthetic correction of nasolabial folds. Each vial of PLLA was reconstituted in 5 mL of SWFI the night before injection.…”
mentioning
confidence: 98%
“…Also, aesthetic effects up to four years with injectable PLLA have been observed, while the claimed aesthetic effect is approximately two years [32]. Between 2008 and 2012, some studies have been published with longer follow-up periods, that is, three to four years [32][33][34][35][36]. The need for this development is illustrated by two studies [37,38] in which it was found that semi-permanent injectable fillers remain in the skin longer than the period claimed by the manufacturer: 18 and 23 months, respectively, while the claims were 12 months.…”
Section: Semi-permanent Tissue Fillersmentioning
confidence: 99%
“…In 22 patients, palpable but non-visible subcutaneous micronodules were observed Not specified/not known [101] Prospective study (n = 116), 25 months follow-up Only 1 case of injection site bruising Treatment related [102] Prospective study (n = 10), 36 months follow-up Short-term complications Not specified/not known [34] Prospective study (n = 65), 36 months follow-up…”
Section: {{mentioning
confidence: 99%